Post mortem [videorecording (DVD)] - Larraín, Pablo; Larraín, Pablo; Castro, Alfredo (Alfredo Arturo Castro Gómez), 1952-; Zegers, Antonia, 1972-; Vadell, Jaime (Kino Lorber, 2012)
In Chile, 1973, during the last days of Salvador Allende's presidency, an employee at a Morgue's recording office falls for a burlesque dancer who mysteriously disappears.